UAV-based measurements of methane emissions from two electrically-driven natural gas compressor stations in China - Tianran Han; Wang Tian; Yuheng Zhang; Jietao Zhou; Yanrong Yang; Keyu Chen; Lei Ren; Chuanfeng Wang; Yufei Huang; Haijiong Sun; Xinyi Chen; Chang Liu; et al. (Environmental Pollution, 2026)

Modification of Lycium ruthenicum pomace dietary fibers: Enhanced physicochemical, structural, and functional properties - Huiling Li; Keyu Tian; Ruiqi Wang; Ruyu Shangguan; Jingna Yang; Nana Yang; Xintao Meng; Xiang Li; Ting Zhang; Hongjie Lei (Food Chemistry, 2026)

Bacillus Cereus C3 Addition Facilitates Carbohydrate Degradation and Earthworm Growth During Vermicomposting of Sewage Sludge - Tiantian Tian; Xinge Cui; Wenxing He; Keyu Liu; Jiran Zhang; Shimin Zhang; Xitian Yang; Kun Wu; Xianqin Jiao; Shuxia Xu (Water, Air, & Soil Pollution, 2026)

Fingerprinting complex mixed oil spills at refineries: Source identification, quantitative source apportionment, and biodegradation assessment - Wang Yu; Jiayi An; Jiuhao Song; Junjie Guan; Keyu Duan; Wei Zhou; Liting Tian; Jie Ma (Water Research, 2025)

Myricetin, as a potential new antiviral agent against Rana grylio ranavirus (RGRV) - Kun Peng; Silu Tian; Le Xu; Yu Yuan; Mingqi Ai; Qibin Jiang; Keyu Zhou; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Fish & Shellfish Immunology, 2025)

A hybrid data-driven and physical model-based approach for predicting the mechanical properties of cable-arrays in flexible cable dual-AUVs systems - Kuo Chen; Zhier Chen; Jiancheng Yu; Kai Ren; Wenkang Jiao; Keyu Chen; Yu Tian; Jie Sun (Ocean Engineering, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

Reduced-order modeling method for flexibly connected dual-AUV system - Kuo Chen; Zhier Chen; Jiancheng Yu; Kai Ren; Wenkang Jiao; Keyu Chen; Yu Tian; Jie Sun (Ocean Engineering, 2024)

Investigation on Phenomics of Traditional Chinese Medicine from the Diabetes - Boxun Zhang; Lijuan Zhou; Keyu Chen; Xinyi Fang; Qingwei Li; Zezheng Gao; Fengmei Lian; Min Li; Jiaxing Tian; Linhua Zhao; Xiaolin Tong (Phenomics, 2024)
With thousands of years of application history, traditional Chinese medicine (TCM) has unique advantages in the prevention of various chronic diseases, and in recent years, the development of TCM has presented a situation where opportunities and challenges coexist. Phenomics is an emerging area of life science research, which has numerous similarities to the cognitive perspective of TCM. Thus, how to carry out the interdisciplinary research between TCM and phenomics deserves in-depth discussion. Diabetes is one of the most common chronic non-communicable diseases around the world, and TCM plays an important role in all stages of diabetes treatment, but the molecular mechanisms are difficult to elucidate. Phenomics research can not only reveal the hidden scientific connotations of TCM, but also provide a bridge for the confluence and complementary between TCM and Western medicine. Facing the challenges of the TCM phenomics research, we suggest applying the State-target theory (STT) to overall plan relevant researches, namely, focusing on the disease development, change trends, and core targets of each stage, and to deepen the understanding of TCM disease phenotypes and the therapeutic mechanisms of herbal medicine.

Fluid tracing and evolution at micron-scale of shales in faulted lake basin: Evidence and constraints from in-situ analysis of analcime - Junran Wang; Chao Liang; Yingchang Cao; Shunyao Song; Keyu Liu; Shengyu Yang; Jinqiang Tian; Danish Khan; Bixiao Xin (Marine and Petroleum Geology, 2024)

Eliminating concentration polarization with gradient lithiophilic sites towards high performance lithium metal anodes under low N/P ratio - Zichun Xiao; Duzhao Han; Yu Fu; Keyu Xie; Wensheng Tian; Chengyong Shu; Kai Xi; Chengxin Peng; Yuping Wu; Shixue Dou; Wei Tang (Chemical Engineering Journal, 2024)

Preface: Petroleum Geology of the Ordos Basin - Jinhua Fu; Keyu Liu; Jingchun Tian; Renchao Yang; Tian Yang (Journal of Asian Earth Sciences, 2023)

Production of marker-free transgenic rice expressing tissue-specific Bt gene - Chengxiang Qiu; Jatinder Singh Sangha; Fengshun Song; Zhiyun Zhou; Ao Yin; Keyu Gu; Dongsheng Tian; Jianbo Yang; Zhongchao Yin (Plant Cell Reports, 2010)